2017
DOI: 10.1002/uog.15982
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a first-trimester screening model for pre-eclampsia in an unselected population

Abstract: The prediction model for PE achieved a similar performance to that obtained in the construction cohort when tested on a subsequent cohort of women, confirming its validity as a predictive model for PE. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…A clear linear independent association between UtA‐PI values in the first trimester and the risk of PE has been reported consistently in previous studies. Hence, the fact that higher mean UtA‐PI values will inevitably lead to an increased screen‐positive rate is expected, if the other markers are held constant and assuming that they should not vary according to UtA‐PI operators.…”
Section: Discussionsupporting
confidence: 66%
“…A clear linear independent association between UtA‐PI values in the first trimester and the risk of PE has been reported consistently in previous studies. Hence, the fact that higher mean UtA‐PI values will inevitably lead to an increased screen‐positive rate is expected, if the other markers are held constant and assuming that they should not vary according to UtA‐PI operators.…”
Section: Discussionsupporting
confidence: 66%
“…The model developed by Scazzocchio et al, 44 which included maternal factors, mean arterial pressure, mean uterine artery-PI, and PAPP-A, achieved detection rates of 69% and 81% for 5% and 10% false-positive rates, respectively, with a recently published internal validation study having reported similar figures. 45 Detection rates reported by the same group 46 using maternal factors, mean arterial pressure, uterine artery-PI, and PlGF in another multiparametric algorithm were 82% and 89% for 5% and 10% false-positive rate, respectively.…”
Section: Principal Findingsmentioning
confidence: 94%
“…Algorithms to calculate the risk for early or late PE have been developed, combining some of these markers with the background risk defined by maternal history. The performance of such a screening is best for early PE requiring delivery before 34 weeks of gestation, but the detection of later PE is also possible [6,[11][12][13] . Placental growth factor (PlGF) is one of the most important firsttrimester biochemical markers for PE.…”
mentioning
confidence: 99%